A Japanese encephalitis virus biological clone with an E gene point mutation exhibits in vitro and in vivo attenuation of neurovirulence - Shu, Pin Yu; Kien, Chai Ong; Soon, Hao Tan; Tomohiro, Ishikawa; David, Perera; Yuan, Teng Hooi; Wong, Kum Thong (Microbiology Society, 2025)
The Japanese encephalitis virus (JEV), a leading cause of viral encephalitis, exists as similar but non-identical biological clones whose genomic variations/mutations may determine neurovirulence. Two biological clones purified from a brain-derived, clinical isolate were tested in vitro for neurovirulence using human neuronal cells (SK-N-MC) and mouse neuronal cells (NIE-115) and in vivo on a footpad-inoculation mouse model. One clone (JEV-M) demonstrated significantly reduced infectivity in both neuronal cells and the mouse model compared to another clone (JEV-V). Of the 2 E gene point mutations in JEV-M, only the T175C mutation, which translates as an E protein residue 59, amino acid tyrosine to histidine change (Y59H), was found to be the neurovirulence determinant as confirmed by testing with infectious clones with or without these mutations. These novel findings could further our understanding of JEV neuropathogenesis and may be useful for future vaccine development.